A novel chaotic DICOM image encryption algorithm based on pseudo-random polyline and rapid diffusion-scrambling. (1st March 2023) - Zhang, Ziying; Teng, Lin
Abstract: This paper proposes a novel chaotic DICOM image encryption algorithm based on pseudo-random polyline and rapid diffusion-scrambling. This paper proposes to preprocess the image twice in the encryption process to ensure that any type of image can be encrypted, including images with negative pixel values, which increases the practicability of the algorithm. Two pseudo-random polylines are generated to segment the image during the encryption process. The pseudo-random polylines are generated from the information of the plaintext image, which ensures that each image produces different pseudo-random polylines and increases the security of the algorithm. In the encryption process, rapid diffusion-scrambling is used to avoid the waste of extra space. And piecewise diffusion and non-adjacent matrix reading are adopted to make the encryption more unpredictable. The scheme is analyzed from the performance indicators such as pixel correlation and key space, and the results demonstrated strong security and performance of the algorithm.